Strengthening Transparency and Accountability of Village-Owned Enterprises (BUMDes) through Community-Based Internal Audit Assistance - Yulisfan Yulisfan; M Irsan Nasution (Universitas 17 Agustus 1945 Semarang, 2025)
Strengthening transparency and accountability in the financial management of Village-Owned Enterprises (BUMDes) is crucial in promoting good village governance. However, many BUMDes still face challenges such as weak record-keeping systems, the absence of internal audits, and limited human resource competencies in financial aspects. This community service activity aims to build an internal audit system as a strategy to improve the financial governance of BUMDes in Pematang Serai Village, Tanjung Pura Sub-District. The approach used is Community-Based Participatory Action Research (CBPAR), which emphasizes active community involvement throughout the process. The stages of the activity include problem identification, internal audit and basic accounting training, preparation of financial SOPs, implementation of the initial audit, and evaluation of the results. The results show that BUMDes administrators are able to independently conduct internal audits, compile cash reports and transaction documentation more systematically, and present the results in village deliberation forums. This activity also succeeded in increasing the capacity of administrators to compile simple digital reports using Excel. Community participation also encouraged the formation of a new culture that is more transparent and open to the process of managing village finances. This activity not only produced administrative outputs but also created institutional transformation that promotes more integrity-based BUMDes governance. The educational-participatory approach in internal audits has proven effective and is feasible to be replicated in other villages with similar conditions as part of efforts to strengthen good governance at the local level.